Solution structure of CCL21 and identification of a putative CCR7 binding site - Love, Melissa (2012)
CCL21 is a human chemokine that recruits normal immune cells and metastasizing tumor cells to lymph nodes through activation of the G protein-coupled receptor CCR7. The CCL21 structure solved by NMR contains a conserved chemokine domain followed by an extended, unstructured C-terminus that is not typical of most other chemokines. A sedimentation equilibrium study showed CCL21 to be monomeric. Chemical shift mapping indicates that the CCR7 N-terminus binds to the N-loop and third β-strand of CCL21’s chemokine domain. Details of CCL21-receptor recognition may enable structure-based drug discovery of novel anti-metastatic agents.